Dynamic alterations in the donkey fecal bacteria community and metabolome characteristics during gestation - Zhang, Zhenwei; Huang, Bingjian; Wang, Yonghui; Zhan, Yandong; Zhu, Mingxia; Wang, Changfa (Frontiers in Microbiology, 2022)
In donkeys, the gestation period is a dynamic and precisely coordinated process involving systemic and local alterations. Both the gut microbiota and its link with blood metabolites are thought to play significant roles in maintaining maternal health and supporting fetal development during the gestation period. This study was conducted to evaluate gut microbiota changes and the correlation with plasma metabolites in Dezhou donkeys during the gestation period. The donkeys were divided into the four following groups according to their pregnancy stages: the non-pregnant (NP), early stage of pregnancy (P1), middle stage of pregnancy (P2), and late stage of pregnancy (P3) groups. A total of 24 (n = 6 per group) samples of donkey feces and plasma were collected. The results showed that the diversity (Shannon index) of fecal bacteria significantly increased throughout the gestation period. The phyla Spirochaetota and Fibrobacterota varied significantly according to the stages of pregnancy (p < 0.05). At the genus level, the abundance of Treponema in pregnant donkeys was greater than that in non-pregnant donkeys (p < 0.05), and the genus Streptococcus reached its maximum abundance in the P2 period (p < 0.05). The abundance of Ruminococcaceae_NK4A214_group and norank_f_norank_o_WCHB1-41 linearly increased with the progression of pregnancy (p < 0.05). In addition, the host plasma metabolome was altered significantly during the gestation period. Testolic acid, estradiol-17beta 3-sulfate, equol 7’-o-glucuronide, equol 4’-o-glucuronide, estrone, estrone 3-glucuronide, and estradiol were the most significant differential enriched metabolites, and they increased gradually as gestation progressed. The altered metabolites were mainly enriched in pathways matched to bile secretion, ABC transporters, amino acid metabolism, protein digestion and absorption, mineral absorption, fatty acid degradation, glycerophospholipid metabolism, and steroid hormone biosynthesis. We also found a significant correlation between the shifts in donkey fecal bacteria and changes in the host metabolism. In summary, this study provided systematic data on the fecal bacterial changes and host plasma metabolism of donkeys throughout pregnancy. The results indicated that host–bacteria interactions during the gestation period influence the host metabolism. These interactions benefit the pregnant donkeys by providing a sufficient supply of nutrients and energy for fetal growth and maternal health.